The 2021 Antarctic Total Eclipse: Ground Magnetometer and GNSS Wave Observations From the 40 Degree Magnetic Meridian. Issue 3 (27th February 2023) - Coyle, S. E.; Hartinger, M. D.; Clauer, C. R.; Baker, J. B. H.; Cnossen, I.; Freeman, M. P.; Weygand, J. M.
Abstract: On 04 December 2021, a total solar eclipse occurred over west Antarctica. Nearly an hour beforehand, a geomagnetic substorm onset was observed in the northern hemisphere. Eclipses are suggested to influence magnetosphere‐ionosphere (MI) coupling dynamics by altering the conductivity structure of the ionosphere by reducing photoionization. This sudden and dramatic change in conductivity is not only likely to alter global MI coupling, but it may also introduce a variety of localized instabilities that appear in both hemispheres. Global navigation satellite system (GNSS) based observations of the total electron content (TEC) in the southern high latitude ionosphere during the December 2021 eclipse show signs of wave activity coincident with the eclipse peak totality. Ground magnetic observations in the same region show similar activity, and our analysis suggest that these observations are due to an "eclipse effect" rather than the prior substorm. We present the first multi‐point interhemispheric study of a total south polar eclipse with local TEC observational context in support of this conclusion. Plain Language Summary: Solar eclipses occur when the Moon intersects the line between the Earth and the Sun. This configuration of Sun and Moon presents a unique opportunity to investigate the effects of the upper atmosphere's electrical conductivity on plasma waves that is independent of season or geomagnetic field orientation. We present observations of plasma waves in the high latitude region of Earth's upper atmosphere during the eclipse on 04 December 2021. These waves are similar to those else‐wise observed near dawn in regions where the magnetic field lines connect to dark skies in one hemisphere and sunlit skies in the other. We suggest that the waves observed during the December 2021 eclipse have a similar generation mechanism to those that occur near dawn, a result of the difference in conductivities between magnetic field‐line footprints. Key Points: A total solar eclipse occurred over Antarctica on 4 December 2021 alongside a geomagnetic substorm Variations in total electron content (TEC) are spatiotemporally correlated with eclipse shadow peak Similar ground magnetic variations are observed in both hemispheres, suggesting eclipse driven waves